2020
DOI: 10.2147/opth.s268327
|View full text |Cite
|
Sign up to set email alerts
|

<p>A 10-Year Retrospective Clinical Analysis of Fungal Keratitis in a Portuguese Tertiary Centre</p>

Abstract: Purpose To determine the microbiological profile, risk factors, treatment and surgical intervention rates of fungal keratitis at a tertiary referral centre. Methods A retrospective review of microbiological and medical records from hospitalised patients treated for fungal keratitis at Centro Hospitalar Universitário de São João from 2009 to 2019 was conducted. Results Overall, 43 patients were included in our study. The mean age of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
(39 reference statements)
0
10
0
3
Order By: Relevance
“…It is most commonly observed in tropical/subtropical countries and regions with prevalent agricultural activity, accounting for 23-63% of all IK cases in these regions [1,10,11]. Compared to bacterial keratitis, FK is more frequently associated with guarded visual prognosis, primarily caused by the significant diagnostic challenge (due to low and slow culture yield), the propensity to deeper infection affecting the posterior cornea, limited antifungal treatment option, and resistance to treatment [4,12]. In addition, many cases of FK usually require therapeutic keratoplasty to achieve complete resolution of the disease, with many of them affected by the recurrence of infection or uncontrolled infection progressing to endophthalmitis and eventuating in evisceration/enucleation [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…It is most commonly observed in tropical/subtropical countries and regions with prevalent agricultural activity, accounting for 23-63% of all IK cases in these regions [1,10,11]. Compared to bacterial keratitis, FK is more frequently associated with guarded visual prognosis, primarily caused by the significant diagnostic challenge (due to low and slow culture yield), the propensity to deeper infection affecting the posterior cornea, limited antifungal treatment option, and resistance to treatment [4,12]. In addition, many cases of FK usually require therapeutic keratoplasty to achieve complete resolution of the disease, with many of them affected by the recurrence of infection or uncontrolled infection progressing to endophthalmitis and eventuating in evisceration/enucleation [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Even for an experienced corneal physician, the diagnostic accuracy via slit lamp image was only about 76% [6]. Consequently, about 12 to 58% of FK patients needed therapeutic keratoplasty or other surgeries to quiet down their infection episodes [7][8][9], and the surgical cure rate of FK was the worst among various MKs [10]. Finally, up to 25% of FK patients might lose their vision [11].…”
Section: Introductionmentioning
confidence: 99%
“…1,10,11 Compared to bacterial keratitis, FK is more frequently associated with guarded visual prognosis, primarily caused by significant diagnostic challenge (due to low and slow culture yield), propensity to deeper infection affecting the posterior cornea, limited antifungal treatment option, and resistance to treatment. 4,12 In addition, many cases of FK usually require therapeutic keratoplasty to achieve completion resolution of the disease, with many of them affected by recurrence of infection or uncontrolled infection progressing to endophthalmitis and eventuating in evisceration / enucleation. [12][13][14][15][16] To date, the majority of the FK studies reported in the literature were conducted in developing or tropical / subtropical regions, including India, China and Nepal, where FK is more prevalent.…”
Section: Introductionmentioning
confidence: 99%
“…4,12 In addition, many cases of FK usually require therapeutic keratoplasty to achieve completion resolution of the disease, with many of them affected by recurrence of infection or uncontrolled infection progressing to endophthalmitis and eventuating in evisceration / enucleation. [12][13][14][15][16] To date, the majority of the FK studies reported in the literature were conducted in developing or tropical / subtropical regions, including India, China and Nepal, where FK is more prevalent. 4,[17][18][19][20][21][22][23] However, the results of those studies may not be readily applicable to populations in developed or temperate regions as the population characteristics, risk factors, underlying causes and management of FK can vary significantly.…”
Section: Introductionmentioning
confidence: 99%